A case series of samar cobra, Naja samarensis Peters, 1861 (Elapidae) envenomation. (February 2023) - Paghubasan, Jonathan; Aoki, Yoshihiro; Tiglao, Patrick Joseph G.; Sarmiento, Marvin Jay; Tan, Mariedel A.; Sarsalijo, Mardie S.; Aquino, Grace Joy B.; Comandante, John David L.; Santamaria, Emelia B.; Takahashi, Kensuke; Smith, Chris; Ariyoshi, Koya; et al.
Abstract: The Samar cobra, Naja samarensis Peters, 1861 is one of the World Health Organization's category I venomous snakes in the Philippines. Although N. samarensis is known to inhabit Eastern Visayas, unlike N. philippinensis in Luzon, no clinical case reports have yet been published in the international literature. No immuno-diagnostic assays have been developed for venomous snakes in the Philippines, even for research purposes. Therefore, identification of the causative snake in hospitals is challenging. In vivo  pre-clinical tests using mice showed that locally-produced antivenom raised against  N. philippinensis  venom ["Purified Cobra Antivenom (PCAV)"] cross-neutralised  N. samarensis  venom. Here, we present five snakebite envenomation cases where causative snakes were confirmed in photos as N. samarensis by an expert local herpetologist. Patients' symptoms and signs varied, from mild to extensive local cytotoxic to systemic neurotoxic envenomation. In one case, venom had been spat into the eye. Out of five patients, two underwent surgical debridement of necrotic tissue at the bite site. One paediatric patient was intubated because of cardiopulmonary arrest. Except for the spitting cobra case, four cases were successfully treated with PCAV and supportive management. These are the first clinical case reports of confirmed N. samarensis envenomation. Graphical abstract: Image 1 Highlights: Naja samarensis envenomation has not been described with the clinical course in the international literature. We report five cases of N. samarensis envenomation identified by the photographs of the causative snakes. One patient required mechanical ventilation, and two underwent surgical debridement on the bite site. Purified Cobra Antivenom raised against N. philippinensis venom was effective in treating neurological symptoms. This is the first report of confirmed N. samarensis envenomation.